(untitled) - Halliday, M. A.K. (London, 1994)
This book remains, thereore, that of giving a comprehensive picture of the English clause together with it interfacings along all dimensions of its environment. But the grammar of a language is open-ended, and every paragraph written here could be expanded into a book (some of them have been)
Keywords: English language,Grammar, comparative and general; Grammar,Function worlds